Pengaruh Model Pembelajaran Means Ends Analisis (MEA) Terhadap Kemampuan Berpikir Kritis Matematika - Ulfah Hernaeny; Ade Afina; Diah Oga Nusantari (Universitas Indraprasta PGRI, 2019)
The aim of the study was to analyze the positive influence of the model learning Means Ends Analysis (MEA) on the ability of critical thinking of mathematics, to students of Madrasah Aliyah Negeri 4 Bekasi. The research methods used in this study are experimental methods, sampling using simple random sampling techniques. The instrument used is the test result of a nine-grain essay about the seven indicators of mathematical critical thinking ability. For scoring, critical thinking skills use zero to four scores. Test data requirements used are liliefors test and Fisher test. From the Liliefors test calculations for experimental classes and the control classes are obtained by normal distribution data and have homogeneous variances. The data analysis technique used is test-T, and based on the calculation of the test-T shows T-hit >T-table, Ho is rejected and H1 accepted so that it can be concluded that there is a positive influence of the model giving learning Means Ends analysis (MEA) to the ability Critical thinking Math, judging by the average thinking skills of mathematical students who are given the model Means Ends analysis (MEA) is higher than the average math critical thinking ability of students who are given expository models.